ANALISIS KESULITAN PENYELESAIAN SOAL GEOMETRI PADA SD ISLAM AL AZHAR 34 MAKASSAR - Herlina; Rukli; Erwin Akib (STKIP Subang, 2023)
Geometry at the elementary school level brings various benefits to students. Firstly, it is a critical stage in the development of spatial abilities. Geometry helps students understand the world around them in different ways. This study aims to analyze the difficulties in solving geometry problems among elementary school students. The research design used is quantitative research with data collection techniques using tests and documentation. The research subjects are fifth-grade students of SD Islam Al Azhar 34 Makassar, consisting of 30 individuals. The research sample consists of 5 students. The results of the study indicate that visual-spatial understanding, perception, interpretation, and mathematical communication skills play a crucial role in students' understanding of geometric concepts. Student A needs to be introduced to the concept of classifying plane figures to improve their spatial understanding, while student B needs a deeper understanding of the types of plane figures. Student C needs to develop mathematical communication skills and pay attention to the instructions of the problems in order to accurately transfer their understanding of concepts. Student D has adequate conceptual understanding but needs to improve their accuracy in solving the final steps. Student E has good conceptual understanding of solving geometry problems but needs to be reminded of the importance of completing all solution steps accurately. An approach that includes introducing the concept of classifying plane figures, deepening understanding of the types of plane figures, developing mathematical communication skills, and paying attention to problem instructions needs to be implemented to enhance students' understanding of geometric concepts and their ability to solve problems accurately.